Power quality and electromagnetic compatibility -The 'simple or not so simple' ubiquitous power supply input stage - - Kennedy, Robert Teasdale; Ismail, Daut (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org